Curbing Inflammation in Burn Patients - Jayme A. Farina; Marina Junqueira Rosique; Rodrigo G. Rosique (Hindawi Limited, 2013)
Patients who suffer from severe burns develop metabolic imbalances and systemic inflammatory response syndrome (SIRS) which can result in multiple organ failure and death. Research aimed at reducing the inflammatory process has yielded new insight into burn injury therapies. In this review, we discuss strategies used to curb inflammation in burn injuries and note that further studies with high quality evidence are necessary.